Chlorpyrifos Induced Disruption in Serum Ca2+, Mg2+ and Pi Electrolytes Level in Freshwater Catfish Heteropneustes fossilis (Bloch) - Pandey, Rakesh Kumar; Verma, Dinesh Kumar; Das, Vijai Krishna (The Scientific Temper, 2020)
Chlorpyrifos is widely used organophosphate (OP) insecticide in agricultural and domestic applications and possess anti-cholinesterase activity. Fishes are inadvertently exposed to pesticides and their metabolic byproducts through runoff water entering the fish habitat. The present study was carried out to observe short-term (24h, 48h, 72h and 96h) and long-term (7d, 14d, 21d and 28d) effect of chlorpyrifos on serum electrolytes (Ca2+, Mg2+ and Pi) in freshwater air-breathing catfish Heteropneustes fossilis. The concentration of chlorpyrifos for short-term exposure was kept at 1.56 mg/l (75% of 96 h LC50) and 0.52 mg/l (25% of 96 h LC50) for long-term. Fishes exposed to sublethal concentrations for short-term (24h, 48h, 72h and 96h) and long-term (7d, 14d, 21d and 28d), exhibited hypocalcaemia, hypophosphatemia and hypermagnesaemia. The present study may be used as valuable biochemical parameters to monitor the health of fish, affected by insecticides.